Understanding Media Convergence in the Digital Age - Monye I. Florence; Muhammad Ridwan (Budapest International Research and Critics University, 2026)
Digital technologies and evolving practices among the audience have turned media convergence into a characteristic of modern communication. This paper evaluates the idea of media convergence by analyzing its historical background, theoretical underpinning, and how it is practiced today in the digital media contexts. It explains the various forms of convergence and the influence of the digital media in transforming the process of creating, distributing and consuming content. The paper describes the way in which audiences interact with converged media platforms and how media influence works in a networked society based on applicable communication theories. The paper further discusses how media convergence has affected journalism, entertainment and education and identifies some of the major issues that have emerged as a result of media convergence including information overload, concentration of media ownership and regulatory complexity. This paper concludes that media convergence is a dynamic and an evolving phenomenon that keeps altering media practices and institutions in an ever more interconnected media environment.